2020
DOI: 10.1055/s-0039-1696997
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, Morbidity, and Prognostic Factors in the Surgical Resection of Brain Metastases: A Contemporary Cohort Study

Abstract: Objective Despite advances in systemic therapy and radiotherapy (RT), neurosurgical resection (NSR) remains a mainstay of the treatment of brain metastases (BMs). Although it is unequivocal in instances of diagnostic doubt, radioresistance, and risk of death due to neurologic causes, NSR may be controversial in other situations. Many aspects related to NSR have not yet been well established, and the primary prognostic indices were proposed only in the last decade. This study evaluates the survival and the morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
2
10
1
Order By: Relevance
“…This finding is coherent with the high incidence of melanoma in the Nordic countries [41]. We found an incidence of synchronous disease at 36 %, similar to other studies that include this variable [5,40].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is coherent with the high incidence of melanoma in the Nordic countries [41]. We found an incidence of synchronous disease at 36 %, similar to other studies that include this variable [5,40].…”
Section: Discussionsupporting
confidence: 92%
“…The incidence rate (2.5/100.00) of first time craniotomy for brain metastases in our cohort is consistent with the findings by Rogne et al in the same demographic region in 2012 (2.6/100.000) [38]. Median age, gender and composition of primary tumors were comparable to the findings of similar European studies [38,39], although international studies report a lower incidence of melanoma in their data [35,37,40]. This finding is coherent with the high incidence of melanoma in the Nordic countries [41].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies reported that the major risk factors associated with CM include incomplete surgical resection of the brain metastasis or abridgment of postoperative radiation therapy. 17 18 One study indicated that the risk of CM was 2.81 times more with piecemeal resection than with en bloc resection. 17 In this study, en bloc resection was impossible because the tumor was strongly adherent to the acoustic-facial nerve and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity and mortality of cholangiocarcinoma (CCA) have increased year by year [1]. Most patients are in advanced stage when they first visit the doctor, and the recurrence rate after CCA is high.…”
Section: Introductionmentioning
confidence: 99%